Use of The International Classification of Functioning, Disability and Health (ICF) as a conceptual framework and common language for disability statistics and health information systems - Kostanjsek Nenad (BMC, 2011)
Abstract A common framework for describing functional status information is needed in order to make this information comparable and of value. The World Health Organization's International Classification of Functioning, Disability and Health (ICF), which has been approved by all its member states, provides this common language and framework. The article provides an overview of ICF taxonomy, introduces the conceptual model which underpins ICF and elaborates on how ICF is used at population and clinical level. Furthermore, the article presents key features of the ICF tooling environment and outlines current and future developments of the classification.